Uptake of indoor residual spray as a malaria vector control strategy among the residents in Migori County, Kenya - Odira, John; Gitahi, Mary W.; Orago, Alloys S. S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally unexpected 219 million malaria cases occurred in 2021, with 90% of these cases happening in the WHO Africa region and unexpected 435,000 malaria transmissions worldwide, with children less than five years being the most-at-risk (61%) of malaria infections (World Malaria Report, 2021). In 2019, IRS coverage was 94.6%. This was reason enough to assess contributing factors leading to not reaching targeted 100% of the households mapped despite massive resources. Methods: The study adopted analytical cross-sectional design. The study area was Migori County (Awendo, Uriri, Rongo, Suna East, Suna West and Nyatike sub counties) where IRS had been implemented in four sessions. The study period November 2021 to April 2022. The respondents sample size was determined using Cochran (1963) for a single population of 1,000 households. The respondents were randomly selected villages from purposively selected Migori County. Kenyatta University Ethics Review Committee and NACOSTI provided ethical clearance. Quantitative data analyzed using SPSS version 2.6 and thematically for qualitative data. A Chi-squared test used to compute statistically significant differences between independent variables at p value <0.05. Results: Some 249 (90%) of the respondents confirmed their houses were IRS- covered while 32 (10%) of the houses were not sprayed because they were not informed in advance (p value <0.000). Conclusions: Using the Chi-squared test of significance the spray operators` arrival time for IRS activities affected the respondents daily calendar of events significantly (p=0.013, <0.05) resulting into respondents’ non-participation and unmet targets.